Saturday Night Live and American TV - Becker, Ron (Professor); Sienkiewicz, Matt; Marx, Nick (Book collections on Project MUSE., 2013)
For over 35 years, ""Live from New York, it's Saturday Night!"" has greeted late night-TV viewers looking for the best in sketch comedy and popular music. SNL is the variety show that launched the careers of a mass of comedians including Dan Aykroyd, Chevy Chase, Chris Farley, Will Ferrell, Tina Fey, Amy Poehler, and Adam Sandler, among others. Week after week, SNL has produced unforgettable sketches and provocative political satire, adapting to changing times while staying true to its original vision of performing timely topical humor. With essays that address issues ranging from race and gender to authorship and comedic performance, this text follows the history of this 36-time Emmy-winning show and its place in the shifting social and media landscape of American television.